Determinants of Organizational Citizenship Behavior with Job Satisfaction Mediation - Diana Mahmudah; Sri Wahyuni; Naelati Tubastuvi; Akhmad Darmawan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Organizational Citizenship Behavior (OCB) is voluntary behavior that supports the effectiveness of the organization. Factors that affect OCB teachers in Islamic educational institutions need to be studied to improve the quality of learning. This study aims to analyze the influence of Islamic Leadership, Work-life Balance, and Organizational Culture on Organizational Citizenship Behavior by Mediating Job Satisfaction in teachers of Islamic educational institutions. The research method uses a quantitative approach with survey design. The research population is 164 teachers with 101 teachers who are determined through purposive sampling with a minimum working period of 2 years. The analysis tool used is Partial Least Square (PLS) with a standard of alpha significance of ten percent. The results of the study show that Islamic Leadership and Organizational Culture have a significant positive effect on OCB. Organizational Culture also has a significant positive effect on Job Satisfaction, which then affects OCB. On the other hand, Islamic Leadership has no significant effect on Job Satisfaction, and Work-life Balance does not have a significant effect on Job Satisfaction or OCB. Job Satisfaction mediates the relationship between Organizational Culture and OCB. The implications of the study show that strengthening Organizational Culture is the main strategy in improving teachers' OCB, both directly and through increasing Job Satisfaction. Islamic leadership effectively encourages OCB directly.